2015
DOI: 10.1063/1.4906803
|View full text |Cite
|
Sign up to set email alerts
|

Advance ratio effects on the flow structure and unsteadiness of the dynamic-stall vortex of a rotating blade in steady forward flight

Abstract: The effect of advance ratio on the flow structures above a rotor blade in dynamic-stall is studied using stereoscopic particle image velocimetry. The dynamic-stall vortex shows a significant velocity component in its core, implying a helical structure progressing radially outboard. In addition, a dual-vortical structure was observed at inboard locations only at high advance ratios. The radial velocity attenuates at outboard locations, in contrast to the expected increase with centripetal acceleration. This att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Phase-averaged PIV (2D and stereo-) is a standard approach for rotor-wake measurements (2D - Reich et al, 2014aReich et al, , 2017stereo -Raffel et al, 2004;Raghav & Komerath, 2015;Reich et al, 2014aReich et al, , 2018. Note that given the strongly three-dimensional flow-field, stereo-PIV is generally preferred to mitigate the influence of out-of-plane particle motions.…”
Section: Instrumentationmentioning
confidence: 99%
“…Phase-averaged PIV (2D and stereo-) is a standard approach for rotor-wake measurements (2D - Reich et al, 2014aReich et al, , 2017stereo -Raffel et al, 2004;Raghav & Komerath, 2015;Reich et al, 2014aReich et al, , 2018. Note that given the strongly three-dimensional flow-field, stereo-PIV is generally preferred to mitigate the influence of out-of-plane particle motions.…”
Section: Instrumentationmentioning
confidence: 99%
“…12,32 The formulation of U R is adopted from the previous study of Lentink and Dickinson 33 and subsequent studies. 3436…”
Section: Foil Kinematics and Numerical Methodsmentioning
confidence: 99%
“…Other studies evaluated the influence of the rotation and showed its great influence on the airloads (Refs. [23][24][25][26][27][28] as the rotation kept the stall vortex closer to the blade surface compared to non-rotating configurations.…”
Section: Journal Of the American Helicopter Societymentioning
confidence: 99%